(untitled) - Gallagher, Michael D. (New York, 2001)
Wireless Telecommunications Networking with ANSI-41 2nd Edition Mike Gallagher and Randall Snyder 575 pages
Keywords: Personal communication service systems,Mobile communication systems,Dịch vụ hệ thống viễn thông cá nhân,Hệ thống viễn thông